Innovative pronominal constructions: a comparison via the PRESEEA-Lima corpus - Samamé Rispa, Anahís (2026)
This preliminary study compares the use of Peruvian Spanish pronominal constructions among two groups of speakers in the city of Lima: descendants of Andean migrants and non-descendants of Andean migrants. Using a sample of data from the PRESEEA-Lima corpus, we analyze the canonical uses of pronominal constructions, as well as those uses that involve innovations with verbs not characterized as canonically pronominal. The analysis of sixteen interviews from the corpus shows that speakers from the group with Andean ancestry produce innovative pronominal constructions not found in the variety spoken by speakers without recent Andean ancestry. Furthermore, compared to the non-Andean group, the former use unstressed personal pronouns more frequently with alternating pronominal verbs. It is concluded that both the innovative uses and the higher frequency of pronominal constructions with alternating verbs are features of the Spanish spoken by the descendants of Andean migrants and can be explained as a case of linguistic convergence.